Diversity management in Vietnam's hospitality industry. Issue 2 (2nd April 2016) - Yap, Matthew H. T.; Ineson, Elizabeth M.
ABSTRACT: This study aims to identify and analyze Vietnamese hospitality students' perceptions of and willingness to employ diversity management in their future workplaces. A total of 273 students, selected purposively from two Vietnamese universities, participated in this research. Five dimensions of diversity management emerged via principal component analysis. Although Vietnamese hospitality students' perceived diversity management positively, they appeared reluctant to employ diversity management in their workplaces in the future. The outlook for the Vietnamese hospitality industry appears to be less than positive with respect to reforming manpower management practices to strengthen their competitive advantage in Asia. This study recommends Vietnamese universities include diversity management in their business curriculum.